Al-Banjari's Concept of Inheritance Based on Gender and Justice and Its Implications for Family Division in Banjar Society - Mu'ammar, Ali (JOURNAL OF ISLAMIC AND LAW STUDIES, 2024)
This research discusses justice in the distribution of Islamic inheritance by examining the concept of ashabah bil ghair in the book of Is'af al-Khaaid by Shaykh Muhammad Syukri Unus. The main focus of this research is how this concept gives inheritance rights to women in the Islamic inheritance system, which is often considered unfair from a gender perspective. Using the literature research method, this study finds that the concept of ashabah bil ghair provides an opportunity for women to get a fairer share of inheritance than the basic rules of faraidh. The study also links the concept to the issue of gender equality in Islamic law and the challenges of its implementation in modern Muslim societies.